The truth, the half-truth, and nothing like the truth: reconceptualizing false allegations of rape - Saunders, Candida L. (Oxford University Press, 2012)
There is a longstanding dispute between criminal justice professionals on the one hand and researchers and commentators on the other regarding the prevalence of false allegations of rape. Prevalence, however, is contingent upon definition. If the various protagonists’ definitions of a ‘false allegation’ do not coincide, it is virtually inevitable that their estimates will diverge. Drawing on original empirical data from in-depth research interviews conducted with police and Crown Prosecutors, this article explores the following important but much neglected question: When criminal justice professionals tell us that false allegations of rape are common, what precisely are they talking about? What ‘counts’ as a false allegation?